Sympathetic nerve activity in normal and cystic follicles from isolated bovine ovary: local effect of beta-adrenergic stimulation on steroid secretion - Ortega Hugo H; Dallard Bibiana E; Diaz Ariel E; Salvetti Natalia R; Paredes Alfonso H; Lara Hernan E (BMC, 2011)
Abstract Cystic ovarian disease (COD) is an important cause of abnormal estrous behavior and infertility in dairy cows. COD is mainly observed in high-yielding dairy cows during the first months post-partum, a period of high stress. We have previously reported that, in lower mammals, stress induces a cystic condition similar to the polycystic ovary syndrome in humans and that stress is a definitive component in the human pathology. To know if COD in cows is also associated with high sympathetic activity, we studied isolated small antral (5mm), preovulatory (10mm) and cystic follicles (25mm). Cystic follicles which present an area 600 fold greater compared with preovulatory follicles has only 10 times less concentration of NE as compared with small antral and preovulatory follicles but they had 10 times more NE in follicular fluid, suggesting a high efflux of neurotransmitter from the cyst wall. This suggestion was reinforced by the high basal release of recently taken-up 3H-NE found in cystic follicles. While lower levels of beta-adrenergic receptor were found in cystic follicles, there was a heightened response to the beta-adrenergic agonist isoproterenol and to hCG, as measured by testosterone secretion. There was however an unexpected capacity of the ovary in vitro to produce cortisol and to secrete it in response to hCG but not to isoproterenol. These data suggest that, during COD, the bovine ovary is under high sympathetic nerve activity that in addition to an increased response to hCG in cortisol secretion could participate in COD development.